HYPOTHYROIDISM AND ALTERATIONS IN HEMATOLOGICAL PARAMETERS - Bodapati, Sunitha; Parvataneni, Radhika; Kakaraparthi, Yasoda devi; punnapu, vijayakumar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The thyroid gland has a very important role in hematopoiesis. Blood disorders are frequently seen in patients with thyroid dysfunction and anemia is more common in them. Thyroid hormones directly affect blood parameters by stimulating erythrocyte precursors and indirectly by enhancing erythropoietin production. The present study was conducted to evaluate the effect of hypothyroidism on different hematological parameters. Methods: This is a prospective observational study which included a total of two hundred individuals. They are enrolled and divided into two equal groups; each group consists of one hundred individuals. The first group consists of one hundred cases of hypothyroidism, whose blood cell indices are compared with one hundred healthy individuals as a control in the second group. Patients with diabetes mellitus, hyperthyroidism, congenital thyroid disorders, thyroid malignancies, hemolytic anemia’s, aplastic anemia, malignancies, leukemias and blood dyscrasias were excluded from the study. Results: The analysis showed a significant difference in the hemoglobin, RBC count, hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), and red cell distribution width (RDW) (p values 0.000, 0.000, 0.000, 0.000, 0.002, 0.000, and 0.022), respectively, while platelets and WBC showed no significant correlation (p values 0.410 and 0.6420). Conclusion: In this study, most of the hematological parameters in hypothyroid cases are significantly low, except RDW levels which are high among them. Platelet count and WBC are less affected in cases when compared with the controls, and the study indicates that anemia is associated with hypothyroidism. The follow-up of patients with thyroid disorders should include the complete blood count and patients diagnosed with anemia should also be evaluated for thyroid disorders before iron therapy or any other therapies. Cases of anemia which are not responding to treatment should be investigated for the possibility of thyroid dysfunction.